Estudos iniciais sobre neurociência e educação infantil - Carrara, Beatriz Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Whereas current research in neuroscience shows that child development, especially in childhood very first, is a differential stage of life, what do the teachers know about this stage of early childhood education? To answer this question it will be necessary to identify, describe and analyze the knowledge that teachers of Early Childhood Education, for students aged 0-3 years have on neuroscience and its application to education of these children. Therefore, the research investigated the advances of science in the context of neuroscience and its relation to pedagogy, since Neuroscience shows that the adult's role in the baby's relations with the external environment - people and objects - are essential to the full and healthy development of the child. Therefore, a qualitative research will be conducted, a case study, based on literature, the theoretical basis will guide the writing of the final report as well as the actions of collection and field analysis. Teachers from two local preschools, 2 private schools and 2 schools associated to Bauru - SP will be interviewed. The interviews were semi-structured, based on selected indicators based on bibliographic contribution on the central theme of research. In view of this, it was possible to observe that most of the teachers with whom the questionnaires were applied do not have adequate knowledge about the relationship between Neuroscience and education. It is hoped that with its realization can verify the interests and training needs of teachers

Considerando que estudos atuais na Neurociência evidenciam que o desenvolvimento infantil, principalmente, na primeiríssima infância, é uma etapa diferencial da vida, o que sabem os professores que atuam nessa etapa da educação infantil? Para responder a tal questão buscou-se identificar, descrever e analisar os conhecimentos que os professores de Educação Infantil, de alunos entre 0 - 3 anos, têm sobre Neurociência e sua aplicação à educação dessas crianças. Para tanto, a pesquisa investigará os avanços da ciência, no âmbito da Neurociência e sua relação com a Pedagogia, uma vez que a mesma aponta o papel do adulto nas relações do bebê com o meio externo - pessoas e objetos, são determinantes para o desenvolvimento saudável e pleno da criança. Para tanto, foi realizada uma pesquisa qualitativa, um estudo de caso, com base em levantamento bibliográfico, a base teórica orientou a escrita do relatório final bem como as ações de coleta e análise de campo. Foram aplicados questionários em professores de 2 escolas municipais de educação infantil, 1 particular e 1 conveniada de Bauru - SP. As entrevistas foram semi estruturadas, baseadas em indicadores selecionados com base no aporte bibliográfico sobre a temática central da pesquisa. Frente a isso, foi possível observar que a maioria dos professores com os quais os questionários foram aplicados não tem o conhecimento adequado acerca da relação da Neurociência com a educação. Esperou-se que com a sua realização possamos verificar os interesses e as necessidades formativas dos professores
Keywords: Educação de crianças; Neurociência cognitiva; Creches; Infância; Neurosciences